The Influence of Work Environment, Career Development and Organizational Commitment on Employee Job Satisfaction. (Study at Bank "M" IT Group) - Alexander Tambunan, Tommy; Iqbal, M. Ali (Dinasti International Journal of Management Science, 2024)
This research aims to determine the influence of the work environment, career development, and organizational commitment on job satisfaction among employees of the IT group of bank "M". The population in this study were 330 employees who worked in the IT Group of Bank "M". The sampling method used in this research is random sampling where the number of samples used is based on the Slovin formula. The population is 330, with a margin of error of 5%, the minimum number of samples taken is 181 employees. The data analysis technique uses Structural Equation Model (SEM) with the help of the SmartPLS program version 3.2.9. The results of this study show a positive and significant influence of the work environment on job satisfaction at IT Bank "M". The positive and significant influence of career development on job satisfaction at IT Bank "M". The positive and significant influence of organizational commitment on employee performance at IT Bank "M".